Learner Organizations in Islamic Education: Integration of Modern Management and Qur'an Values in West Java Islamic Boarding Schools - Rafi Jauhari Robbani; Muhammad Yamin Arif; Kamaluddin; Zakariya (Solo Universal Journal of Islamic Education and Multiculturalism, 2025)
Objective: This study aims to analyze the application of learning organizations through the integration of modern management and Qur'an values in West Java Islamic boarding schools. The focus is on improving the quality of learning, institutional management, and innovation culture. Theoretical framework: This research combines the theory of the Senge learner organization with the values of the Qur'an, such as deliberation, amanah, and itqan. This framework supports adaptive and sustainable management of Islamic education. Literature review: Previous studies have shown that learning organizations improve educational performance through collaboration and continuous learning. However, the integration of Islamic values and modern management in Islamic boarding schools has not been thoroughly studied. Methods: The research uses a qualitative approach with case studies in several Islamic boarding schools in West Java. Data was collected through interviews, observations, and documentation, and then analyzed using the Miles and Huberman model. Results: The results of the study show that the integration of modern management and the values of the Qur'an increases the effectiveness of learning, collaboration, and innovation of Islamic boarding schools. Spiritual values also strengthen organizational commitment and decision-making. Implications: Pesantren need to implement learning organizations to improve the quality of education management. The integration of Qur'anic values and modern management can support sustainable institutional transformation. Novelty: This research offers a learning organization model based on Qur'an values that is integrated with modern management. This model makes a theoretical and practical contribution to the development of Islamic education management.